Protective effect of anti-SUAM antibodies on Streptococcus uberis mastitis. (December 2015) - Almeida, Raúl; Kerro-Dego, Oudessa; Prado, María; Headrick, Susan; Lewis, Mark; Siebert, Lydia; Pighetti, Gina; Oliver, Stephen
Abstract In the present study, the effect of anti-recombinantStreptococcus uberis adhesion molecule (SUAM) antibodies againstS. uberis intramammary infections (IMI) was evaluated using a passive protection model. Mammary quarters of healthy cows were infused withS. uberis UT888 opsonized with affinity purified anti-rSUAM antibodies or hyperimmune sera. Non-opsonizedS. uberis UT888 were used as a control. Mammary quarters infused with opsonizedS. uberis showed mild-to undetectable clinical symptoms of mastitis, lower milk bacterial counts, and less infected mammary quarters as compared to mammary quarters infused with non-opsonizedS. uberis . These findings suggest that anti-rSUAM antibodies interfered with infection of mammary gland byS. uberis which might be through preventing adherence to and internalization into mammary gland cells, thus facilitating clearance ofS. uberis, reducing colonization, and causing less IMI.